2019
DOI: 10.3390/vaccines7040170
|View full text |Cite
|
Sign up to set email alerts
|

A Recombinant La Sota Vaccine Strain Expressing Multiple Epitopes of Infectious Bronchitis Virus (IBV) Protects Specific Pathogen-Free (SPF) Chickens against IBV and NDV Challenges

Abstract: Infectious bronchitis (IB) and Newcastle disease (ND) are two major infectious diseases that are a threat to the domestic poultry industry. In this study, we successfully generated a recombinant LaSota candidate vaccine strain, rNDV-IBV-T/B, which expresses a short, synthetic, previously identified IBV S1 multi-epitope cassette using the reverse genetic system. The recombinant virus was propagated in nine-day-old embryonated chicken eggs for 20 passages and genetic stability was confirmed by whole genome DNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…Therefore, a novel vaccine should consider protection against challenges by different serotype IBVs. Our previous studies demonstrated that DNA vaccine or recombinant NDVs expressing the IBV multiple epitope cassette S-T/B, consisting of three pieces of B cell neutralizing epitopes and four pieces of BF2-restricted T cell epitopes, offer potency against homologous and heterologous IBV strain challenges [ 24 , 26 ]. However, the main shortcoming of NDV-vectored bivalent vaccines is that their thermolabile and low temperature characteristics might not be properly maintained during mass vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, a novel vaccine should consider protection against challenges by different serotype IBVs. Our previous studies demonstrated that DNA vaccine or recombinant NDVs expressing the IBV multiple epitope cassette S-T/B, consisting of three pieces of B cell neutralizing epitopes and four pieces of BF2-restricted T cell epitopes, offer potency against homologous and heterologous IBV strain challenges [ 24 , 26 ]. However, the main shortcoming of NDV-vectored bivalent vaccines is that their thermolabile and low temperature characteristics might not be properly maintained during mass vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…The antigenicity for expressing the multiple epitope cassette S-T/B of the rLS-T-HN-T/B strain was analyzed by Western blotting according to a previously reported method [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other studies reported a recombinant NDV expressing IBV S protein generated using reverse genetics technology to fully protect from challenge with virulent NDV and IBV [170,171]. Similarly, an rNDV-IBV-T/B multiple-epitope NDV vectored vaccine developed using reverse genetics, protected against IBV and NDV [172]. More so, R-H120-HN/5a an IBV/NDV recombinant vaccine developed by reverse genetics reportedly induced humoral immune response and provided protection against challenge with virulent IBV and NDV.…”
Section: Ib and Nd Vaccine Developmentmentioning
confidence: 99%
“…Many of these genetic constructs [ 100 , 101 ] are based on a Beaudette strain (GI-1) backbone, which lacks of pathogenicity and would prevent residual effects of the attenuation process, others focus on the deletion of pathogenicity-associated genes [ 96 ], obtaining attenuation without the loss of protection. Recombinant vaccines have been produced also by cloning IBV proteins into the backbone of other viruses (Fowl Adenovirus, FAdV [ 102 , 103 ]; Newcastle disease virus, NDV [ 104 , 105 ]; avian Metapneumovirus, aMPV [ 106 ]), achieving a variable degree of protection. However, individual administration was still required for these vaccines, thus limiting their practicability.…”
Section: Relevant Factors For Ibv Controlmentioning
confidence: 99%